Quiet eye duration is responsive to variability of practice and to the axis of target changes - Horn, R. R.; Okumura, M. S.; Alexander, M. G. F.; Gardin, F.; Sylvester, C. T. (Research Quarterly for Exercise and Sport, 2012)
We tested the hypothesis that quiet eye, the final fixation before the initiation of a movement in aiming tasks, is used to scale the movement's parameters. Two groups of 12 participants (N = 24) threw darts to targets in the horizontal and vertical axes under conditions of higher (random) or lower (blocked) target variability. Supporting our predictions, random practice and target changes in the vertical axis led to longer quiet eye duration than did blocked practice and target changes in the horizontal axis. Our data suggest that quiet eye is not simply a mediating factor in accuracy, but is responsive to the task's programming demands, being influenced by the necessity to reparameterize the movement from one trial to the next.